MATEMATIK TERMINLAR DERIVATSIYASINING LEKSIK-SEMANTIK USULI - Ruzmetova, O.A. (SCIENCE and SOCIETY, 2021)
The article discusses the lexical-semantic method of forming some terms in the field of mathematics and discusses their comparative analysis of the lexical-semantic method of forming words in the Uzbek and English languages.
Keywords: lexical derivation; word formation; lexical-semantic method; derivative word; affixation; suffixation; prefix